2017
DOI: 10.33087/aksara.v1i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kohesi Leksikal Dalam Majalah Patriotik LPM Universitas Batanghari Edisi Xvi Juli-September Tahun 2016

Abstract: Tujuan penelitian ini adalah untuk mendeskripsikan unsur kohesi leksikal yang terdapat dalam majalah Patriotik LPM Universitas Batanghari edisi Juli-September Tahun 2016. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Data pada peneitian ini adalah wacana yang terdapat dalam majalah Patriotik Edisi XVI Juli-September Tahun 2016. Teknik pengumpulan data yang digunakan pada penelitian ini adalah teknik baca dan catat. Adapun teknik analisis yang digunakan pada penelitian ini adalah kajian isi.Berda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…In the discussion part of lexical cohesion in this research, repetition is the lexical cohesion aspect that appears the most. It was in line with the previous research findings, such as those conducted by Mirzapour and Ahmadi (2011), Pernando and Rahima (2017). However, there had been researching that was not in line with the research previously mentioned, such as the research done by Ali (2010), who analyzed a short story entitled "The Killer," in which his research indicated that lexical cohesion in the form of antonym had the highest percentage of the whole aspect of lexical cohesion, namely 32.5%.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In the discussion part of lexical cohesion in this research, repetition is the lexical cohesion aspect that appears the most. It was in line with the previous research findings, such as those conducted by Mirzapour and Ahmadi (2011), Pernando and Rahima (2017). However, there had been researching that was not in line with the research previously mentioned, such as the research done by Ali (2010), who analyzed a short story entitled "The Killer," in which his research indicated that lexical cohesion in the form of antonym had the highest percentage of the whole aspect of lexical cohesion, namely 32.5%.…”
Section: Discussionsupporting
confidence: 77%
“…A study analyzing the grammatical and lexical cohesion of other written discourse, such as a novel, speech scripts, short story, essay, scientific article, magazine, and newspaper have also been conducted ( i.e. Alacron & Morales, 2011;Ali, 2010;Dang, 2020;Hidayat, 2016;Malah & Rashid, 2017;Mandarani, 2020;Ma'wa & Mirahayuni, 2010;Mizopour & Ahmadi, 2011;Pernando & Rahima, 2017;Sari, Ermanto, & Agustina, 2018;Sudani & Tika, 2017;Warid & Lail, 2021;Widiatmoko, 2015). For example, Ma'wa and Mirahayuni (2010) conducted a study on analyzing lexical cohesion in two short stories.…”
Section: Studies On Grammatical and Lexical Cohesionmentioning
confidence: 99%
See 2 more Smart Citations
“…Namun, kohesi leksikal bukan hanya berfokus kepada bentuk tetapi juga makna. Hal ini juga disampaikan oleh Pernando (2016: 2) bahwa penda kohesi tidak hanya berhubungan dengan bentuk tetapi juga berhubungan dengan makna. Artinya bahwa hubungan makna baik makna leksikal maupun makna gramatikal, perlu diwujudkan secara terpadu dalam kesatuan yang membentuk teks.…”
unclassified